Micelle-mediated extraction and neutron activation determination of nanogram levels of vanadium in seaweeds - Serfor-Armah, Y.; Carboo, D.; Akuamoah, R.K.; Chatt, A. (Journal of Radioanalytical and Nuclear Chemistry, 2018)
A simple one-step micelle-mediated extraction, commonly called cloud point extraction, method was developed for the preconcentration of vanadium in red, brown and green seaweeds. The recovery of vanadium under the optimized conditions of pH 3.7, [PAN/TAN] = 1×10−4 M, [PONPE-20] = 0.1% (m/v), ionic strength = 0.05 M KNO3, and a temperature of 41 °C was > 99%. Vanadium was assayed by neutron activation analysis using the Dalhousie University SLOWPOKE-2 reactor facility. The detection limits for vanadium varied from 0.6 to 3.9 µg kg−1 depending on the sample. The method was validated using certified reference materials. Mass fractions of vanadium in seaweeds ranged from 0.009 to 55.4 mg kg−1. © 2018, Akadémiai Kiadó, Budapest, Hungary.
Keywords: Cloud point extraction; Neutron activation; Seaweeds; Vanadium